Sago starch-based edible film with ascorbic acid for active food packaging: article - Ak Munan, Melissa Laila; Hamidon, Fariza (2019)
This study aimed to analyse and evaluate the effect of the addictive of ascorbic acid(AA) on the properties of the produced sago starch-based edible film. Tests were run on the films with and without ascorbic acid to determine the mechanical strength, thickness, solubility of films, antioxidant activity and color. The higher concentration of AA in sago starch film shows the higher solubility compared to film without AA. It was also shown the decreasing in tensile strength and increasing in elongation on film. The water vapor permeability of films with the AA concentration was lowest. Besides, the concentration of AA in films affect antioxidant activity as it has higher percentage of radical scavenging activity (98.5%) meanwhile the colour of the film with AA is yellowish as the degradation of AA presence in film.